KOMUNIKASI EFEKTIF DALAM PRAKTEK KOLABORASI INTERPROFESI SEBAGAI UPAYA MENINGKATKAN KUALITAS PELAYANAN - Noor Ariyani Rokhmah; Anggorowati Anggorowati (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract: The purpose of this study Literature review was to determine the effective communication in practice interprofesi collaboration will improve the quality of service. Literature review research method is done by performing a search at EBSCO publishing articles, Google Search, PubMed, Sciencedirect.com with the selected keywords that interprofessional Collaboration practice, effective communication, hospital, service quality. The search was performed by limiting the issue of 2005 - 2015. The results of the literature search that good quality services depend on professionals who work together in interprofessional teams. Communication interprofesional used is SBAR (Situation-Background-Assessment Recommendation).Keywords: effective communication, collaboration interprofesi, quality of service practices